Improving the Production of Well Irrigated Cauliflower (Brassica OleraceaL. Var. Botrytis,Cv. Snowball Y. Imp) by Foliar Spraying of some Growth Regulators - Abdel, Caser G. (Sulaimani Journal for Pure and Applied Sciences, 2009)
Three different experiment were conducted on Snowball Y. IMP Cauliflower Cultivar. Seeds were sown in seedbed to produce transplants. The obtained transplants were planted on furrows, and then they were sprayed twice, 2 weeks after transplanting and 4 months latter with either gibberellic acid (GA3) at rates of 0.0, 20, 30 and 40mg.l-1, indole-3-butyric acid (IBA) at rates of 0.0, 20, 30 and 40mg.l-1, or naphthalene acetic acid (NAA) at rates of 0.0, 20, 30 and 40mg.l-1 to improve the production of snowball Y. IMP cauliflower cultivar which was irrigated whenever 25% of soil water capacity is depleted to a soil depth of 30cm. The results revealed that snowball Y. IMP cauliflower cultivar required supplementary irrigation of 327.6 mm, besides 254.3 mm rainfalls, during the entire growing season. GA3 application substantially increased the yield of cauliflower particularly 40 mg.l-1 which gave the highest yield (3.65 kg.m-2), as compared to check (2.44 kg.m-2). Regression analysis displayed that cauliflower yield responses to GA3 application could be estimated by the following positive linear equation (Yield kg.m-2 = 2.35836 + 0.0313786(GA3rate)). IBA application substantially increased the yield of cauliflower particularly 40 mg.l-1 which gave the highest yield (7.61 kg.m-2) as compared to untreated control (5.74 kg.m-2). Regression analysis displayed that cauliflower yield responses to IBA application could be estimated by the following cubic equation (Yield kg.m-2 = 5.7375 + 0.599098(IBA rate) - 0.0436278(IBA rate)**2 + 0.0007442(IBA rate)**3). NAA application substantially increased the yield of cauliflower particularly 30 mg.l-1 which gave the highest yield (3.15 kg.m-2 ) as compared to check (1.4 kg.m-2). Regression analysis displayed that cabbage yield responses to NAA application could be estimated by the following positive linear equation (Yield kg.m-2 = 1.85084 + 0.0377673(NAA rate).
Keywords: Irrigation; IBA; GA3; Cauliflower; Growth Regulators